Ant community diversity in two agrosystems in Bejaia wilaya (Northern Algeria) - Henine-Maouche, Anissa; Guergouz, Wissem; Moudache, Thiziri (Sociobiology, 2022)
The present work studied the diversity of Formicidae in two agrosystems of Bejaia, a lemon orchard located at INRAA and an orange orchard located at Amizour. We used the transect method by combining three (3) sampling methods: Barber Pots or Pitfall, Bait, and manual capture. We identified 18 ant species representing 11 genera and three subfamilies: Dolichoderinae (Tapinoma magnum), Formicinae (Cataglyphis, Camponotus, Lasius, and Plagiolepis), and Myrmicinae (Messor, Aphaenogaster, Crematogaster, Pheidole, Tetramorium, and Temnothorax). The species richness was 13 species in the Oued Ghir’s site and 12 species in Amizour’s site. At INRAA, Dolichoderinae and Myrmicinae have the same proportions (43.95 and 43.17%, respectively) followed by Formicinae (12.88%). In Amizour, Formicinae showed the higher frequency (40.28%), followed by Dolichoderinae and Myrmicinae (30.47 and 29.25%, respectively). In the INRAA lemon orchard Tapinoma magnum was the dominant species with a relative abundance of 43.95%, whereas in Amizour the predominance is attributed to the Cataglyphis viatica with a relative abundance of 39.05%.